THE ROLE OF ULTRASOUND IN THE DIAGNOSIS OF LIVER ECHINOCOCCOSIS IN CHILDREN (Herald of the National Children's Medical Center, 2024)
Echinococcal disease is a parasitic disease accompanied by the development of single and multiple cystic formations of various sizes in the liver. Over the past decades, Uzbekistan has maintained a steady trend towards an increase in the incidence of liver echinococcosis, characterized by the extent of the lesion and a long-term chronic course. Detection of this disease in the early stages of development is difficult due to the lack of clear clinical symptoms and complaints of the patient. Most often, patients seek medical help when the cyst reaches a significant size or there are signs of its complications, which in most cases are detected by ultrasound examination.